Angiotensin-(1-7) Inhibits Thrombin-Induced Endothelial Phenotypic Changes and Reactive Oxygen Species Production via NADPH Oxidase 5 Downregulation - Pai, Wan-Yu; Lo, Wan-Yu; Hsu, Todd; Peng, Ching-Tien; Wang, Huang-Joe (Frontiers in Physiology, 2017)
Background and Aims: The angiotensin-(1-7)/angiotensin-converting enzyme 2/Mas receptor axis counter-regulates the detrimental effects of angiotensin II. Beneficial effects of angiotensin-(1-7), including anti-inflammation, oxidative stress reduction, and anti-thrombosis, have been reported. Previous studies documented that ramipril decreased thrombin generation in human hypertension and that the anti-thrombotic effects of captopril and losartan were angiotensin-(1-7)-dependent, suggesting an interaction between thrombin and angiotensin-(1-7). However, it is not clear whether angiotensin-(1-7) can alleviate the endothelial phenotypic changes induced by thrombin. We have previously documented cytoskeleton remodeling, cell adhesion, and cell migration as dominant altered phenotypes in thrombin-stimulated human aortic endothelial cells (HAECs). In this study, we investigated whether angiotensin-(1-7) can modulate thrombin-induced phenotypic changes. Furthermore, we investigated whether NAPDH oxidase 5 (Nox5)-produced reactive oxygen species (ROS) play a significant role in angiotensin-(1-7)-mediated phenotypic changes. Methods: HAECs were pretreated with 100 nM angiotensin-(1-7) for 1 h, followed by stimulation with 2 units/mL thrombin for different times. Immunofluorescent assay, monocyte adhesion assay, wound-healing assay, ROS assay, real-time PCR, Western blotting, and Nox5 siRNA transfection were conducted. HAECs were pretreated with the ROS scavenger N-acetylcysteine (NAC) to determine whether thrombin-induced phenotypic changes depended on ROS production. Results: Angiotensin-(1-7) prevented thrombin-induced actin cytoskeleton derangements, monocyte adhesion, and migratory impairment. Nox5 siRNA transfection confirmed that thrombin-induced Nox5 expression stimulated ROS production and increased HO-1/NQO-1/ICAM-1/VCAM-1 gene expression, all of which were decreased by angiotensin-(1-7). Phenotypic changes induced by thrombin were prevented by N-acetylcysteine pretreatment. Conclusion: Angiotensin-(1-7) prevents actin cytoskeleton derangement, monocyte adhesion, and migration impairment induced by thrombin via downregulation of ROS production. In addition, thrombin-induced Nox5 expression is involved in the production of ROS, and angiotensin-(1-7) decreases ROS through its inhibitory effect on Nox5 expression.